“Der Burschen Herrlichkeit”? Old and New Ways of Examining the History of German University Students (1810-1945). A Research Report - Stickler, Matthias (CIAN-Revista de Historia de las Universidades, 2022)
This research report attempts to show the basic lines of student history research in relation to the period from 1810 to 1945. It is thus primarily concerned with the period that is referred to in university history research as the “classical phase” (Peter Moraw). After an overview of fundamental questions about the era, it gives an overview of the history of student fraternities, whose importance cannot be overestimated. However, since student history is not limited to fraternity history, it then describes the relationship between student and fraternity history since the 19th century as a kind of elective affinity. In this context, particular attention is paid to the not always easy relationship between professional researchers and laypersons interested in student history, often members of student fraternities. The following part is devoted to the “Sonderweg theory” in student history, i.e., the thesis that student fraternities were a particularly characteristic form of expression of the “German Sonderweg”. Finally, the last part deals in detail with more recent tendencies in student historiography since the late 1990s, especially on Catholic student life, student violence, Jewish students and anti-Semitism, as well as female students and gender-historical approaches. As an important desideratum, genuine cultural aspects of student history are identified. Nonetheless, student history has nowadays developed into a flourishing branch of university history.
Keywords: Germany; student fraternities; “student historians”; student self-organization; university history; student history